Efficacy of Coronary Stenting Versus Ballon Angioplasty in Small Coronary Arteries - Asad Khan, Muhammad Shahab Uddin Khalil, Abdul Latif, Muzdalfa Parvez, Zarmina Ikram (Pakistan Journal of Medical & Health Sciences, 2022)
Background and aim: The most common approach of percutaneous myocardial revascularization is stent placement. In de novo focal lesions found in big native arteries, balloon angioplasty had lower efficacy than coronary stenting. However, the usefulness of stenting in small arteries remains debatable. The purpose study aimed to compare the efficacy of coronary stenting vs. balloon angioplasty in small coronary arteries. Patients and Method: This comparative study was carried out on 132 patients with lesion in small coronary arteries (reference diameter <3mm) in the department of Interventional Cardiology, MTI- Hayat Abad Medical Complex, Peshawar from 16th January 2021 to 15th July 2022. Patients were arbitrarily assigned to stent implantation and standard balloon angioplasty. Study protocol was approved by research and ethical committee. Each individual provided written informed consent. The rates of clinical event were evaluated within 1 year. Descriptive statistics was carried out in SPSS version 26. Results: Of the total patients, there were 80 (60.6%) male and 52 (39.4%) were females. Both groups were assigned 66 patients and had similar baseline characteristics and angiography data. Based on treatment analysis, the major adverse cardiac events (MACEs) and angiographic success rate were similar: 5.2% and 96.8% in coronary stenting versus 5.9% and 92.4% in balloon angioplasty group respectively. About 4.2% patients underwent abrupt closure changes within 30 days. Stenting convened the substantially larger lumen (1.52 mm vs. 1.32 mm, p<0.001) at 6 months and larger post-procedural lumen diameter (2.31 vs. 1.82 mm, p<0.001) as compared to balloon angioplasty. The incidence of restenosis was found 36% and 56% in coronary stenting and balloon angioplasty respectively. The survival rate (event-free) was achieved in 79% and 69% (p=0.021) in coronary stenting and angioplasty respectively. Conclusion: The present study found that optimum balloon angioplasty with preliminary stenting may be a viable therapeutic option for small coronary arteries lesions. Restenosis was found to be 36% and 56% in coronary stenting and balloon angioplasty, respectively. Keywords: Restenosis, Small coronary arteries, Balloon angioplasty, Coronary stenting